Development and Evaluation of Portal do Zumbido: A Novel Telehealth Approach to Tinnitus - de Matos,Izabella Lima (2021)
Abstract Introduction Tinnitus is a prevalent symptom in audiological clinics, and the speech therapist participates in the assessment, diagnosis, and intervention of tinnitus. A range of studies have been developed with the aim to promote auditory health, and telehealth is an option for this purpose. Objective The aim of the present study was to develop and assess a virtual platform for tinnitus management for speech therapists. Methods The present study provided a distance-learning-course, with the aid of Portal do Zumbido, available in the following electronic address: zumbido.fob.usp.br. Infographics were available for download, and modules were made to comprise the introduction to the symptoms, assessment, and intervention for tinnitus. Results Speech therapists of different regions of Brazil received an e-mail invitation to participate and to assess the platform, 46 of whom registered. From the 46 speech therapists registered, 38 assessed the virtual platform with the aid of a questionnaire about the theoretical content and then answered a motivational research sheet (MRS). The speech therapists correctly answered 90% and 100% of the questions in the questionnaire and in the MRS, respectively, which may indicate that the professionals positively absorbed the content; thus, the content was considered to be impressive when the MRS was analyzed. Conclusion Portal do Zumbido was developed and is available for access in the following electronic address: zumbido.fob.usp.br. Furthermore, the platform received a positive assessment by the speech therapists who participated in the present study.